The Role of PKK in Sustainable Community Empowerment - Zuhri, Muchamad Syaifuddin; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
The general background while community empowerment is widely studied, the specific contributions of PKK remain underexplored. Specific background this study focuses on PKK's role in Tambak Kalisogo Village, particularly within sustainable community empowerment programs. Knowledge Gap Existing literature lacks a comprehensive analysis of PKK's multifaceted role in community development initiatives. Aims this research aims to elucidate the various roles of PKK, including its functions as a motivator, facilitator, mobilizer, and regulator in community empowerment. Results the findings reveal that PKK effectively organizes activities, provides guidance in food processing, ensures quality in production, and complies with governmental regulations, thus significantly impacting community welfare. Novelty this research contributes to the field by presenting a detailed examination of PKK's diverse functions in fostering community development and enhancing the economic capabilities of women. Implications Strengthening PKK's initiatives can further improve community welfare, encouraging women's participation in economic activities, and leading to more prosperous and resilient families. Highlights: PKK functions acts as a motivator, facilitator, mobilizer, and regulator in community initiatives. The study demonstrates PKK's effectiveness in enhancing local economic welfare through various programs. Strengthening PKK's efforts fosters women's participation, contributing to improved family income and welfare. Keywords: PKK, Empowerment, Welfare, Community, Economy